Interpretation of Several Key Phenomena Peculiar to Nano Dielectrics in terms of a Multi-core Model - Tanaka, T. (2006 IEEE Conference on Electrical Insulation and Dielectric Phenomena, 2006)
Some of the major dielectric phenomena observed in polymer nanocomposites are explained in terms of a multi-core model proposed by the author. They include characteristics associated with low field conductivity, high field conduction, permittivity, loss tan delta, the threshold field for space charge formation and EL inception, the increase in PD endurance and in treeing lifetime, and even a newly found crossover phenomenon. This model is characterized by individual and collective roles of multi-cores. The latter is related to carrier injection and tree growth at high electric field.